If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12 = 3(x + 4) + 3x Reorder the terms: -12 = 3(4 + x) + 3x -12 = (4 * 3 + x * 3) + 3x -12 = (12 + 3x) + 3x Combine like terms: 3x + 3x = 6x -12 = 12 + 6x Solving -12 = 12 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -12 + -6x = 12 + 6x + -6x Combine like terms: 6x + -6x = 0 -12 + -6x = 12 + 0 -12 + -6x = 12 Add '12' to each side of the equation. -12 + 12 + -6x = 12 + 12 Combine like terms: -12 + 12 = 0 0 + -6x = 12 + 12 -6x = 12 + 12 Combine like terms: 12 + 12 = 24 -6x = 24 Divide each side by '-6'. x = -4 Simplifying x = -4
| 446=x^2 | | (9x-2)+(7x+14)=180 | | -17(-13-12q)= | | 54=3g | | -15x+10=15x-10 | | Y-8=2(x-6) | | 9t-13t=24 | | 4(n+4)-6u=14 | | 5(4+2x)1(8x-12)=68 | | 30-23=6k-13 | | (8x+4)+(4x+2)=180 | | -54x^5-81x^4+2x^2+3x= | | -11=4y+13 | | 3x+8=2x-8 | | 6x*x+7= | | (8x+4)=(4x+2) | | 8x+5x+4+9=4x+4+8x | | 2i=16 | | 2y-7Y=10 | | 8x-10x=2x-4 | | 5x+4-9=180 | | 6+7x=26+3x | | -16=-4(2x-8) | | 7x+4=6y+5 | | 6(2a)=3 | | 15x+12=7x-52 | | 9*8+10= | | 5(w-4)-8w=4 | | d+d+d=9 | | 17+7=a+8 | | 9*8-10= | | 2x-6=6x-14 |